1999
DOI: 10.1002/(sici)1097-4571(1999)50:12<1083::aid-asi7>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Museum informatics and collaborative technologies: The emerging socio-technological dimension of information science in museum environments

Abstract: The museum offers a starting point from which to examine the fundamental nature of collaborative work and interdisciplinary scholarship. This article examines the socio‐technological impact of introducing advanced information technology into the Spurlock Museum, a museum of world history and culture at the University of Illinois. It addresses the implementation of such methodologies as computer‐supported cooperative work (CSCW) and computer‐mediated communication (CMC) in the museum environment. Discussions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…TE and TA best reflect consumer opinions of technology and are proposed in the following model for testing. Marty (1999), Sullivan et al (2007), and Smith (2002) clearly supported the notion of TE having a positive and direct relationship to TA and confirmed that computer self-efficacy significantly influences TA. As a result of this research, it is then hypothesized that:…”
Section: Technology Acceptance: Intention To Use and Adoptmentioning
confidence: 99%
“…TE and TA best reflect consumer opinions of technology and are proposed in the following model for testing. Marty (1999), Sullivan et al (2007), and Smith (2002) clearly supported the notion of TE having a positive and direct relationship to TA and confirmed that computer self-efficacy significantly influences TA. As a result of this research, it is then hypothesized that:…”
Section: Technology Acceptance: Intention To Use and Adoptmentioning
confidence: 99%
“…A considerable amount of research has been done with regard to the role of interactive technology in museum management (Marty, 1999;Lagrosen, 2003;Knell, 2003;Nickerson, 2004;Vom et al, 2005;Lachaud & Passebois, 2008;Bonacasa, 2011;Hume & Mills, 2011;Hogsden & Poulter, 2012). Nevertheless, there has been little research conducted specifically on the role of mobile applications for museums.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As museum professionals come to rely on information technologies in the operations of their organizations, the museum itself becomes an interesting site to study how the collaborative activities of the museum staff are influenced by new technologies (Marty, 1999a). Several researchers have begun to explore the notion of the museum as a complex, sociotechnical environment.…”
Section: Integrated Information Systems and Information Infrastructuresmentioning
confidence: 99%